Clinicopathological profile of Papillary thyroid carcinoma in a tertiary cancer hospital in Nepal - Parajuli, Samyam; Gautam, Dej Kumar; Karki, Anil Bikram; Karmacharya, Dilip; Shrestha, Amar; Neupane, Bijay; Pandey, Greta; Chalise, Kamana; Devkota, Subash (Nepalese Journal of Cancer, 2023)
Background: Differentiated thyroid cancers (DTC), including papillary thyroid carcinoma (PTC), are on the rise. This study provides a detailed examination of PTC cases in a tertiary care cancer hospital in Nepal, aiming to understand its clinical characteristics and treatment patterns. We conducted a retrospective analysis of PTC, including demographics, features of tumor, and treatment modalities. Methods: A retrospective cross-sectional study assessed cases of PTC from January 2022 to December 2022. Patient data were collected and analyzed, focusing on demographics, tumor attributes, and treatment approaches. Results: Among 105 patients, females were predominant (female-to-male ratio 5.2:1), and ethnic diversity was observed. Most patients were from Lumbini Pradesh. The mean age was 40.78 years. Fine-needle aspiration cytology (FNAC) showed Bethesda VI as the most common classification. Primary treatment involved total thyroidectomy (76.25%). Classical PTC was the major histopathological variant (78.1%). Tumors were frequently located in the right lobe (55.25%). Unifocal tumors were prevalent (74.28%), with an average size of 2.74 cm. Lymph node metastasis occurred in 49.5% of patients. Intermediate-risk patients constituted the majority (53.5%). Conclusion: This study offers crucial insights into PTC's clinical spectrum in Nepal, aiding in tailored patient care strategies. The findings contribute to informed decision-making for enhanced treatment outcomes.